Talent vs training - Tucker, R. (The Science of Sport, 2017)
The Talent Series: Strategy, tactics and then science Talent ID Video Series, Part 1: Fundamental concept and definition Talent ID & Management Series, Part 2: Accepted inefficiencies Talent ID & Management Part 3: Imperfect tools & sensible science Talent ID & Management: The 10,000 hour "rule" and talent Talent ID & Management Part 5: Early vs Late Specialisation? Talent ID & Management Part 6: The Relative Age effect Transformation in SA sport: Dear Minister… Talent ID & Development: IAAF Level 5 and USATF Level 3 lectures